1975
DOI: 10.1111/j.1476-5381.1975.tb06939.x
|View full text |Cite
|
Sign up to set email alerts
|

ANTIARRHYTHMIC, HAEMODYNAMIC AND METABOLIC EFFECTS OF 3α‐AMINO‐5α‐ANDROSTAN‐2β‐OL‐17‐ONE HYDROCHLORIDE IN GREYHOUNDS FOLLOWING ACUTE CORONARY ARTERY LIGATION

Abstract: 1The antiarrhythmic, haemodynamic and metabolic effects of a new amino steroid, ORG6001, have been investigated in experimental acute myocardial infarction in anaesthetized greyhounds. 2 ORG6001 administered either intravenously (1-10 mg/kg) or orally (50 mg/kg) significantly reduced the incidence of ventricular ectopic beats in the first 30 min after ligation of the left anterior descending coronary artery. 3 In dogs pretreated with ORG600 1, metabolic changes indicative of myocardial ischaemia (lactate produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Introduction We have previously demonstrated that 3a-amino-5a-androstan-2p-ol-17-one (ORG 6001) administered intravenously or orally is capable of preventing the early ventricular dysrhythmias that result from coronary artery ligation in anaesthetized greyhounds (Marshall & Parratt, 1975). In addition, there was evidence that some of the metabolic indices of myocardial ischaemia (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Introduction We have previously demonstrated that 3a-amino-5a-androstan-2p-ol-17-one (ORG 6001) administered intravenously or orally is capable of preventing the early ventricular dysrhythmias that result from coronary artery ligation in anaesthetized greyhounds (Marshall & Parratt, 1975). In addition, there was evidence that some of the metabolic indices of myocardial ischaemia (e.g.…”
mentioning
confidence: 99%
“…However, these subsequent occlusions (up to six) produced similar changes in the ST-segment elevation in control dogs. already reported (Marshall & Parratt, 1975) (Maroko et al, 1971), with the degree of change in coronary blood flow and with the extent of anaerobic metabolism (Karlsson, Templeton & Willerson, 1973). This present study has shown that an aminosteroid antidysrhythmic drug, ORG 6001, is capable of reducing ST-segment elevation produced by short coronary occlusions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Org 6001 (3a-amino-5x-androstan-2p-ol-17-one HCI) protects against arrhythmias induced by coronary artery ligation after both acute (Marshall & Parratt, 1975) and prolonged oral pretreatment (Kane, Lepran, McDonald, Parratt & Szekeres, 1980). It may, therefore, be a useful prophylactic agent in preventing sudden cardiac death resulting from reinfarction.…”
Section: Introductionmentioning
confidence: 99%
“…Marshall & Parratt (1975) (H. Jansen, personal communication). Org 6001 has been categorized as a class 1 antidysrhythmic drug on the basis of its ability to reduce the maximum rate of depolarization of phase zero (MRD) of the rabbit cardiac muscle action potential (Salako, Vaughan Williams & Wittig, 1976).…”
Section: Introductionmentioning
confidence: 99%